2016
DOI: 10.1016/j.bica.2015.09.007
|View full text |Cite
|
Sign up to set email alerts
|

Artwork creation by a cognitive architecture integrating computational creativity and dual process approaches

Abstract: The paper proposes a novel cognitive architecture (CA) for computational creativity based on the Psi model and on the mechanisms inspired by dual process theories of reasoning and rationality. In recent years, many cognitive models have focused on dual process theories to better describe and implement complex cognitive skills in artificial agents, but creativity has been approached only at a descriptive level. In previous works we have described various modules of the cognitive architecture that allows a robot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 46 publications
0
9
0
2
Order By: Relevance
“…the Double Diamond model (Design Council, 2005), further decomposition of the creative process has been limited by the lack of granularity in this conceptualisation. In this context, dual-process theory provides a basis for further decomposing divergent/convergent creative cognition (Augello et al, 2016). Specifically, it allows researchers to elaborate a number of mechanisms underpinning creative production.…”
Section: Iced19mentioning
confidence: 99%
See 1 more Smart Citation
“…the Double Diamond model (Design Council, 2005), further decomposition of the creative process has been limited by the lack of granularity in this conceptualisation. In this context, dual-process theory provides a basis for further decomposing divergent/convergent creative cognition (Augello et al, 2016). Specifically, it allows researchers to elaborate a number of mechanisms underpinning creative production.…”
Section: Iced19mentioning
confidence: 99%
“…The structure provided by System 1 and System 2 elaborates and connects critical procedural concepts such as 'process awareness' (Valgeirsdottir et al, 2016) and uncertainty perception (Christensen and Ball, 2017) as well as more specific concepts of divergence/convergence, association and fixation, inspiration and intuition (Badke-Schaub and Eris, 2014). Further, the robustness of dual-process theory makes it suitable for simulation and thus forms the basis for important emergent discussions of how to model and structure understanding of creativity (Augello et al, 2016) and activity in design (Cash and Kreye, 2017). As such, it can be concluded that dual-process theory provides a common lens for understanding a range of related design concepts and thus provides a basis for integrating these discussions in a structured manner.…”
Section: Iced19mentioning
confidence: 99%
“…Este modelo (Figura 1) difiere de los clásicos (Dewey, 1910;Wallas, 1926), al enfatizar la no linealidad del pensamiento en su proceder. Este proceso implica operaciones divergentes y convergentes, capaces de involucrar hasta cuatro actividades (exploratorias, reflexivas, tácitas y analíticas) que, desencadenadas por impulsos y motivaciones, generan actos creativos (Augello et al, 2016).…”
Section: Memoria Creativaunclassified
“…3.1). Systems whose conceptual processing activity is based on the dual process approach have been also recently investigated in the area of computational creativity of robotic agents [Augello et al (2016)].…”
Section: Dual-process Oriented Conceptual Representationsmentioning
confidence: 99%